Learning, Curriculum and Life Politics: The Selected Works of Ivor F. Goodson - Goodson, Ivor F. (RoutledgeFalmer, 2005)
In this book, Ivor Goodson brings together 20 key writings in one place. Starting with a specially written Introduction, which gives an overview of Ivor's career and contextualizes his selection within the development of the field, the chapters cover:· Curriculum history and policy· Classroom pedagogy and strategies for professional development· Life history, narrative and educational changeThis book not only shows how Ivor's thinking developed during his long and distinguished career; it also gives an insight into the development of the fields to which he contributed.In the World Library of Educationalists, international scholars themselves compile career-long collections of what they judge to be their finest pieces - extracts from books, key articles, salient research findings, major theoretical and/practical contributions - so the world can read them in a single manageable volume. Readers will be able to follow the themes and strands of their work and see their contribution to the development of a field, as well as the development of the field itself.
Keywords: compétence; curriculum; réforme